HUBUNGAN ANTARA KONSEP DIRI DENGAN PERILAKU ASERTIF REMAJA DESA PANGEMPON KECAMATAN BAWANG KABUPATEN BATANG - Rahma Oknavia Merida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background that prompted this research is that there is low assertive behavior in teenagers due to having a poor view of themselves. The aim to be achieved in this research is to determine the relationship between self-concept and assertive behavior in youth youth groups in Pangempon Village, Bawang District, Batang Regency. This type of research is quantitative correlational research. The population used in this research was 35 teenagers from the Pangempon Village, Bawang District, Batang Regency. The sampling used was a saturated sample so that the total population used as a sample was 35 people. The data analysis used in this study used the Pearson product moment correlation test with the help SPSS 26. The result of data analysis in this study showed a significance of 0,000 < 0,05 which is a relationship between self concept and assertive behavior in adolescents. The value of correlation coefficient that has been obtained of 0,672 can be interpreted as a relationship between self concept and assertive behavior in adolescent, which has a potent category. That is, the higher the self concept in adolescents, the higher the assertive behavior, and vice versa. Apart from that, there is a contribution of 45.2% where self-concept is one of the factors in the emergence of assertive behavior and the remaining 54.8% is another factor that has not been researched.